SUPPLY CHAIN PERFORMANCE MEASUREMENT USING SCOR 12.0 IN SPORT SHOES COMPANY - Arinda Soraya Putri; Wahyu Aji Prabowo (Jurnal Ilmiah Teknik Industri, 2023)
A manufacturing company in Indonesia creates sports shoes under the particular brand is still having trouble with a number of issues, including late raw material deliveries from suppliers, production that falls short of expectations, and delayed product delivery to customers. The performance of the supply chain must therefore be measured. The study assesses the importance of supply chain performance within the organization and offer recommendations for improvement to raise supply chain performance within the organization. Analytical Hierarchy Process (AHP) and Supply Chain Operation Reference (SCOR) 12.0 are used to gauge supply chain performance. The outcomes revealed that supply chain performance’s value at 77,539. Improvements are required to increase the company's supply chain performance because three KPIs have low weights, the percentage of orders for raw materials that are delivered on time, the price of purchasing raw materials, and the cost of returning item. Corrective actions carried out by the company include arranging materials neatly in the warehouse, providing sufficient lighting, maintaining air humidity, keeping hands clean when holding shoes, checking glue on the upper shoes so that open bonding does not occur, giving penalties to suppliers who are late, and giving training to reduce material damage.